Tumor-infiltrating monocytes/macrophages promote tumor invasion and migration by upregulating S100A8 and S100A9 expression in cancer cells - Lim, S; Yuzhalin, A; Gordon-Weeks, A; Muschel, R (Nature Publishing Group, 2016)
Myeloid cells promote development of distant metastases, but little is known about the molecular mechanisms underlying this process. Here we have begun to uncover the effects of myeloid cells on cancer cells in a mouse model of liver metastasis. Monocytes/macrophages, but not granulocytes, isolated from experimental liver metastases stimulated migration and invasion of MC38 colon and Lewis lung carcinoma cells. In response to conditioned media from tumor-infiltrating monocytes/macrophages, cancer cells upregulated S100a8 and S100a9 mRNA expression through an ERK-dependent mechanism. Suppression of S100A8 and S100A9 in cancer cells using shRNA significantly diminished migration and invasion in culture. Downregulation of S100A8 and S100A9 had no effect on subcutaneous tumor growth. However, colony size was greatly reduced in liver metastases with decreased invasion into adjacent tissue. In tissue culture and in liver colonies derived from cancer cells with knockdown of S100A8 and S100A9, MMP2 and MMP9 expression were decreased, consistent with the reduction in migration and invasion. Our findings demonstrate that monocytes/macrophages in the metastatic liver microenvironment induce S100A8 and S100A9 in cancer cells, and that these proteins are essential for tumor cell migration and invasion. S100A8 and S100A9, however, are not responsible for stimulation of proliferation. This study implicates S100A8 and S100A9 as important mediators of tumor cell aggressiveness, and highlights the therapeutic potential of S100A8 and S100A9 for interference of metastasis.